2019
DOI: 10.1123/japa.2018-0341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Judo Training on Functional Fitness, Anthropometric, and Psychological Variables in Old Novice Practitioners

Abstract: This study aimed to investigate the effects of a 4-month judo training (1 hr session, biweekly) on physical and mental health of older adults (69.7 ± 4.2 years). Participants (N = 30) were assigned to a judo novice practitioners group (n = 16) or a control group (n = 14), which did not receive any training. Before and after the program, they underwent anthropometric (body mass index and waist and hip circumferences); functional fitness (upper and lower body flexibility and strength, coordination); and psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
154
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(157 citation statements)
references
References 38 publications
1
154
0
2
Order By: Relevance
“…Every study obtained 60% or more of the scale's total score (15 points), as can be observed in Table 1. One study obtained a score of 9/15 [46], two obtained 10/15 [42,45], one obtained 11/15 [37], four obtained 12/15 [41,44,47,48], three obtained 13/15 [38,40,43], and one obtained 14/15 [39].…”
Section: Methodological Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…Every study obtained 60% or more of the scale's total score (15 points), as can be observed in Table 1. One study obtained a score of 9/15 [46], two obtained 10/15 [42,45], one obtained 11/15 [37], four obtained 12/15 [41,44,47,48], three obtained 13/15 [38,40,43], and one obtained 14/15 [39].…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Twentytwo studies were excluded because they were not OCS interventions; twelve because the mean age of the sample was less than 60 years of age; thirteen because they did not correspond to the research object, i.e., they were not centered on the health outcomes of older adults; three because the full texts were inaccessible; five because they were not randomised-controlled trials; and four because they were reviews or case studies. After this process, the total number of studies that met the selection criteria was equal to twelve [37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Studies Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Judo has specific effects on bone health 2 and can be practised safely until older age. 3 Competitive Judo matches involve two contestants, wearing the judogi (Judo uniform) and fighting each other using different techniques. These techniques can be classified into throwing techniques (nage-waza), in which the thrower keeps the standing position or loses balance in order to project the faller, and grappling technique (katame-waza), which includes holding (osaekomi-waza), joint (kansetsu-waza), and strangulation (shime-waza) techniques.…”
Section: Introductionmentioning
confidence: 99%